2020
DOI: 10.1002/anie.202006562
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Imaging of Subsurface Interstitial Hydrogen and Insights into Surface Reactivity of Palladium Hydrides

Abstract: Resolving interstitial hydrogen atoms at the surfaces and interfaces is crucial for understanding the mechanical and physicochemical properties of metal hydrides. Although palladium (Pd) hydrides hold important applications in hydrogen storage and electrocatalysis, the atomic position of interstitial hydrogen at Pd hydride near surfaces still remains undetermined. We report the first direct imaging of subsurface hydrogen atoms absorbed in Pd nanoparticles by using differentiated and integrated differential pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 25 publications
3
40
0
Order By: Relevance
“…As a first step, we determined the most favorable interstitial site occupied by a hydrogen atom in a "bulk" fcc Pd containing 108 atoms. As seen in previous works 54,55 , among the two possible interstitial sites, the octahedral one is the most stable in the bulk, even if the energy difference between both interstitial sites is weak (around 0.1 eV). This stable configuration is not surprising since the octahedral site is larger than the tetrahedral one.…”
Section: Location Of Trapped H In Nanoparticlessupporting
confidence: 70%
“…As a first step, we determined the most favorable interstitial site occupied by a hydrogen atom in a "bulk" fcc Pd containing 108 atoms. As seen in previous works 54,55 , among the two possible interstitial sites, the octahedral one is the most stable in the bulk, even if the energy difference between both interstitial sites is weak (around 0.1 eV). This stable configuration is not surprising since the octahedral site is larger than the tetrahedral one.…”
Section: Location Of Trapped H In Nanoparticlessupporting
confidence: 70%
“…Along with other supporting techniques and simulations, certain atomic columns observed by microscopy were interpreted as interstitial boron atoms. In 2020, Gan et al 47 reported that the use of a differentiated and integrated differential phase contrast technique (dDPC and iDPC) in aberration-corrected STEM can even directly visualise atomic columns of hydrogen that correspond to interstitial tetrahedral sites in the Pd-H system, which was also supported by simulated dDPC images. On the basis of the result, they claimed that hydrogen can also occupy tetrahedral interstitial sites, which is in agreement with previous NPD studies 48 and theoretical calculations 49 .…”
Section: Probing Interstitial Light Elements With Electronsmentioning
confidence: 89%
“…11,12,19,20 Usually, those nonmetallic atoms with small atomic radii can easily permeate and occupy the interstitial sites including octahedral (O-site) and/or tetrahedral (T-site) sites of the Pd host lattice. [21][22][23] Moreover, the incorporation of these nonmetallic atoms can expand the lattice spacing of Pd. 11,12,24 Theoretically, the incorporation of nonmetallic atoms into interstitial sites within metal lattices can lead to materials with increased hardness and chemical stability considering the fact the interstitial atoms can strengthen the metal-metal bonding.…”
Section: Fundamental Aspects Of Pdl X Nanomaterialsmentioning
confidence: 99%
“…Some organic molecules, including N,N-dimethylformamide (DMF), n-butylamine, formaldehyde or acetaldehyde, can be catalyzed by Pd materials to produce H 2 , which is then dissociated on the Pd surface to generate H adatoms that can permeate into the Pd lattice and finally occupy the interstitial sites to form PdH x . 21,34,[52][53][54] Based on this, PdH x nanomaterials can be obtained by heating Pd nanomaterials or Pd(II) in the above organic solvent, which acts as both a H source and a solvent. Importantly, the formation of trace oxide during this process can passivate the original PdH x surface, thus endowing PdH x with excellent stability.…”
Section: Nanoscalementioning
confidence: 99%